Dolutegravir in the long term in children and adolescents: frequent virological failure but rare acquired genotypic resistance. Issue 10 (8th August 2021) - Frange, Pierre; Blanche, Stephane; Veber, Florence; Avettand‐Fenoel, Veronique
Abstract: Objectives: Although widely recommended, data about dolutegravir efficacy in HIV‐1‐infected children/adolescents are scarce, limited to short‐term follow‐up and mainly extrapolated from studies in adults with good adherence to treatment. This study aimed to provide long‐term data about the risk of virological failure (VF) and acquired genotypic resistance in children and adolescents receiving dolutegravir. Methods: This retrospective monocentric study included 134 paediatric patients who received a dolutegravir‐based regimen for ≥ 12 months in 2014–2020. Virological failure was defined as not achieving a plasma viral load (pVL) < 50 copies/mL within 3 months of dolutegravir initiation or as experiencing virological rebound ≥ 50 copies/mL. Results: Most of the subjects were antiretroviral therapy‐experienced (90.3%), naïve from integrase inhibitors (90.3%) and displayed virological suppression at baseline (63.4%). Their median (interquartile range, IQR) age was 12.0 (8.0–15.8) years. Genotypic susceptibility score of the new regimen was ≥ 2 in 96% of cases. Median (IQR) follow‐up was 34 (22–50) months. Virological failure occurred in 43 people (32.1%), more frequently where the baseline pVL was ≥ 50 copies/mL (67.4% vs . 22.0%, P  < 0.01). M184V/I mutations in the reverse transcriptase gene were newly detected in three people with VF. Resistance to dolutegravir (mutations G118R and E138A in the integrase gene) emerged in one adolescent (0.7% of subjects, 2.3% of those with VF). Conclusions: Whereas VF is relatively common on dolutegravir in the paediatric population, regimens associating dolutegravir with more than one fully active drug were associated with a low rate of emergent drug resistance. This result strengthens the recommendation of dolutegravir as part of preferred combinations in children/adolescents.